PECULIARITIES OF INTERTEXT AND INTERCULTURE PARADIGM OF JOSEPH ROT PROSE - Monolatii, T. P. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2019)
The article analyses interpretation of Joseph Roth prose in the context of intertextuality as a literary means. It is determined by the author’s strategy and studied the aesthetic issues that are fundamental to his work. Intertextuality proves a postmodern phenomenon of reinterpretation of classic and new texts, giving them new meanings and establishing parallels with modern literature, which is reflected in an adequate interpretation of their genre and stylistic forms, the interpretation of philosophical concepts, iconic fictional and aesthetic phenomena. So in fiction there is an additional dimension – intercultural component of the artistic world of the text. This theoretical approach is extremely productive, especially in the study of works of those authors; the arts are rooted in different spheres of human existence, formed on the border of their own cultures, languages, historical and national traditions. A good representative of “intercultural” narrative strategy is Joseph Roth. Thus, under conditions of intertextual interaction, the literary work becomes part of a broad intertextual space that covers not only literary, but also outside of literature forms of expression, and any text is in various “dialogical” relations with other texts that fill this space with different language codes that are represented in this space.